Prove of hydrogen formation through direct potential measurements in the rolling slit during cold rolling. Issue 1 (4th April 2014) - Merzlikin, S.V.; Wildau, M.; Steinhoff, K.; Hassel, A.W.
<x content-type="archive" xml:space="preserve">Abstract</x> In this work, direct potential measurements during cold rolling of zinc and X20Cr13 stainless steel were carried out in the rolling slit to follow the tribologic and galvanic mechanisms of hydrogen formation and absorption on the surface of the working rolls made of DHQ1 grade steel. An Ag/AgCl in 3.5 M KCl reference microelectrode was used to record the open circuit potential of the electrochemical system roller-product immersed into commercially relevant electrolyte (rolling emulsion) with a pH value of 4.5 and an electric conductivity 46 mS cm-1. The potential shift into either negative or positive direction of the rolls-product system gives information on the processes taking place at the surface in the course of the friction. A detailed discussion of the in-situ potentiometry experiments reveals a stationary situation established between the destruction and repassivation of the surface structures during continuous cold rolling accompanied with intensive hydrogen evolution. Galvanic coupling of the working rolls with the product significantly intensifies the hydrogen embrittlement related problems of the rolls. Atomic hydrogen is adsorbed on the surface and exhibits a pressure supported absorption into the rolls during their whole lifetime.